Influence of Spinal Cord Integrity on Gait Control in Human Spinal Cord Injury. (July 2016) - Awai, Lea; Bolliger, Marc; Ferguson, Adam R.; Courtine, Grégoire; Curt, Armin
Background . Clinical trials in spinal cord injury (SCI) primarily rely on simplified outcome metrics (ie, speed, distance) to obtain a global surrogate for the complex alterations of gait control. However, these assessments lack sufficient sensitivity to identify specific patterns of underlying impairment and to target more specific treatment interventions. Objective . To disentangle the differential control of gait patterns following SCI beyond measures of time and distance. Methods . The gait of 22 individuals with motor-incomplete SCI and 21 healthy controls was assessed using a high-resolution 3-dimensional motion tracking system and complemented by clinical and electrophysiological evaluations applying unbiased multivariate analysis. Results . Motor-incomplete SCI patients showed varying degrees of spinal cord integrity (spinal conductivity) with severe limitations in walking speed and altered gait patterns. Principal component (PC) analysis applied on all the collected data uncovered robust coherence between parameters related to walking speed, distortion of intralimb coordination, and spinal cord integrity, explaining 45% of outcome variance (PC 1). Distinct from the first PC, the modulation of gait-cycle variables (step length, gait-cycle phases, cadence; PC 2) remained normal with respect to regained walking speed, whereas hip and knee ranges of motion were distinctly altered with respect to walking speed (PC 3). Conclusions . In motor-incomplete SCI, distinct clusters of discretely controlled gait parameters can be discerned that refine the evaluation of gait impairment beyond outcomes of walking speed and distance. These findings are specifically different from that in other neurological disorders (stroke, Parkinson) and are more discrete at targeting and disentangling the complex effects of interventions to improve walking outcome following motor-incomplete SCI.